Strategies of Omnibus Law Under the Hierarchical Legislation Framework: A Review of Theoretical and Practical Implications - Ihsanul Maarif (Journal of Law, Politic and Humanities, 2024)
The implementation of the Omnibus Law in Indonesia, particularly the Job Creation Omnibus Law, has raised several challenges related to the principles of the hierarchy of legislation and legal certainty. The Omnibus Law, which combines various regulations from different levels of law without regard to hierarchical order, has the potential to create legal uncertainty, undermine the legal order, and reduce protections for workers' rights and the environment. This study aims to examine the compatibility of the Omnibus Law method with the principles of Indonesia's hierarchy of legislation and identify its impact on legal certainty. This research employs a normative legal method with approaches that include legislation, conceptual analysis, and comparison, as well as analyzing data from various primary and secondary legal sources. The research findings indicate that the Omnibus Law does not fully align with the principles of the hierarchy of legislation outlined by Hans Kelsen and Hans Nawiasky, and it creates regulatory overlaps that disrupt the legal system's stability. The implications of this research emphasize the importance of adjusting the Omnibus Law concept to better align with Indonesia's legal framework, as well as the need for more detailed implementing regulations to minimize legal uncertainty across various sectors.